Functional MRI of Letter Cancellation Task Performance in Older Adults - Deng, Ivy D.; Chung, Luke; Talwar, Natasha; Tam, Fred; Churchill, Nathan W.; Schweizer, Tom A.; Graham, Simon J. (Frontiers in Human Neuroscience, 2019)
The letter cancellation task (LCT) is a widely used pen-and-paper probe of attention in clinical and research settings. Despite its popularity, the neural correlates of the task are not well understood. The present study uses functional magnetic resonance imaging (fMRI) and specialized tablet technology to identify the neural correlates of the LCT in 32 healthy older adults between 50-85 years of age, and further investigates the effect of healthy aging on performance. Subjects performed the LCT in its standard pen-and-paper administration and with the tablet during fMRI. Performance on the tablet was significantly slower than on pen-and-paper, with both response modes showing slower performance as a function of age. Across all ages, bilateral brain activation was observed in the cerebellum, superior temporal lobe, precentral gyrus, frontal gyrus, and occipital and parietal areas. Increasing age correlated with reduced brain activity in the frontal gyrus, superior parietal lobe, precentral gyrus, postcentral gyrus, anterior cingulate and cerebellum. Better LCT performance was correlated with increased activity in the frontal gyrus, and reduced activity in bilateral cerebellum, occipital gyrus, left calcarine sulcus and left inferior temporal gyrus. The brain regions activated are associated with visuospatial attention and motor control, and are consistent with the neural correlates of LCT performance previously identified in lesion studies.